MHD Effect on Porous Wide Composite Slider Bearing Lubricated with a Couplestress Fluids - Biradar Kashinath (Japanese Society of Tribologists, 2015)
A Magnetohydrodynamic effect on porous composite slider bearing lubricated with couple stress fluids is numerically analyzed. A modified Reynolds equation has been derived taking into magnetic field in the couple stress fluid lubrication of wide porous composite slider bearing. The closed forms of expressions are obtained for the non-dimensional fluid film pressure, load carrying capacity, frictional force and coefficient of friction. It found that when a magnetic field is applied to each particle experience force which causes the colloidal homogeneous suspension to move en masse significant MHD effects causes the fluid pressure, load carrying capacity, frictional force and coefficient friction. The effects of permeability parameter are depicted in the various figures. The results are compared with nonmagnetic case.